Meningkatkan Hubungan Sosial Mahasiswa Dengan Pendekatan Layanan Konseling Kelompok - Enny Fitriani; Nurasyah Nurasyah; Rini Fadhillah Putri; Johannes Johannes; Suprianto Suprianto (Guidance : Jurnal Bimbingan dan Konseling, 2022)
This study aims to improve the social relations of pharmacy students which have been seen to be inharmonious. With the development of information technology, they interact more often with their gadgets and make the classroom environment seem foreign to all of them. This is what makes researchers interested in doing research. This research was conducted at STIKes Indah Medan, pharmacy study program with a total sample of 10 people. The method used in this study is a quasi-experimental research design with pre-test and post-test using a Likert scale questionnaire instrument with the hypothesis tcount = 7,626, while the ttable value with d.b = N – 1 = 10 – 1 = 9 at the real level = 5 % obtained by 2.262. So that tcount > ttable or 7,626 > 2,262. Based on this, it can be stated that group counseling services can improve student social relations